Proceedings of the Ocean Drilling Program, 139 Scientific Results 1994
DOI: 10.2973/odp.proc.sr.139.230.1994
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Formation of a Massive Sulfide Deposit, Middle Valley, Northern Juan de Fuca Ridge (Site 856)

Abstract: Studies of sulfide cores from Site 856, Middle Valley, northern Juan de Fuca Ridge, established the vertical zonation of a large inactive oceanic massive sulfide deposit. Zone 1 consists mainly of pyritic massive sulfide with minor sphalerite and magnetite (0 to 28 mbsf in Hole 856H and 0 to 40 mbsf in Hole 856G). Compared with the rest of the deposit, this zone is strongly enriched in Zn and a large number of trace metals (in particular Cd, Mn, Sn, and Sb), and in elements contained in gangue minerals (Si, Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Barrett et al (1990) firstly reported several massive sulfide-sulfate samples from the Southern Explorer Ridge, which have relatively flat REE patterns with positive Eu anomalies and negative Ce anomalies. Such REE patterns are also found in massive sulfides from Middle Valley on the Juan de Fuca Ridge (Krasnov et al, 1994) and oxides from the TAG mound (Mills and Elderfield, 1995). Analysis of hydrothermal plume particles has shown that the particles close to an active vent-field exhibit REE patterns of both seawater and vent-fluid characteristics (i.e., negative Ce anomalies and positive Eu anomalies), whereas at increasing dispersion, seawater characteristics become dominant (German et al, 1999) Mitra et al, 1994).…”
Section: Exhalative Hydrothermal Fluids Responsible For Massive and Smentioning
confidence: 89%
See 1 more Smart Citation
“…Barrett et al (1990) firstly reported several massive sulfide-sulfate samples from the Southern Explorer Ridge, which have relatively flat REE patterns with positive Eu anomalies and negative Ce anomalies. Such REE patterns are also found in massive sulfides from Middle Valley on the Juan de Fuca Ridge (Krasnov et al, 1994) and oxides from the TAG mound (Mills and Elderfield, 1995). Analysis of hydrothermal plume particles has shown that the particles close to an active vent-field exhibit REE patterns of both seawater and vent-fluid characteristics (i.e., negative Ce anomalies and positive Eu anomalies), whereas at increasing dispersion, seawater characteristics become dominant (German et al, 1999) Mitra et al, 1994).…”
Section: Exhalative Hydrothermal Fluids Responsible For Massive and Smentioning
confidence: 89%
“…End member hydrothermal fluids at active black smoker vents have enriched REE concentrations (10~10,000 × seawater concentrations) and chondrite normalized REE patterns with a large positive Eu anomaly, no Ce anomaly, and enrichment in the LREE compared to the HREE (Klinkhammer et al, 1994;Mitra et al, 1994;Bau and Dulski, 1999). Massive sulfides, anhydrites, barites and oxides collected on the sea floor, such as those from the Red Sea, the Southern Explorer Ridge, the East Pacific Rise, Middle Valley on the Juan de Fuca Ridge and TAG, also show positive Eu anomalies and LREE-enriched patterns (Barrett et al, 1990;Krasnov et al, 1994;Mills and Elderfield, 1995;German et al, 1999;Bach et al, 2003). Positive Eu anomalies are reported in some samples of massive sulfides from ancient massive sulfide deposits, such as the Bathurst district of New Brunswick, Broken Hill in Australia, Sullivan in British Columbia, Kuroko in Japan and so on (Lottermoser, 1989;Jiang et al, 2000;Slack et al, 2000;Terakado and Walker, 2005).…”
Section: Exhalative Hydrothermal Fluids Responsible For Massive and Smentioning
confidence: 99%
“…2 and 3) indicate a subhorizontal base to the massive sulfide lens, which is interpreted as a time horizon marking the onset of exhalative hydrothermal activity at this site some 220,000 to 140,000 years ago (Mottl et al, 1994). Textural evidence suggests that the bulk of the sulfide was precipitated at the sea floor, with little evidence for the replacement or intercalation of sediment Krasnov et al, 1994). The primary minerals were dominantly pyrrhotite with less abundant Cu-Fe sulfide (isocubanite) and Zn sulfide (sphalerite ± wurtzite).…”
Section: Bent Hill Massive Sulfide Depositmentioning
confidence: 89%
“…This assemblage together with fluid-inclusion trapping temperatures suggests precipitation from fluids venting at 350°to 400°C, precluding formation from the lower temperature fluids presently venting from the ODP mound . Low As, Sb, and Mo concentrations in the primary sulfides, as well as Pb and He isotope constraints, indicate that the mineralizing fluids attained their chemical and thermal characteristics dominantly through reaction with basaltic basement rather than with overlying sediments Krasnov et al, 1994;Stuart et al, 1994;Stuart et al, 1999;Bjerkgård et al, 2000;Cousens et al, 2002). The deposit has been extensively recrystallized to pyrite ± magnetite by hydrothermal zone refining Krasnov et al, 1994).…”
Section: Bent Hill Massive Sulfide Depositmentioning
confidence: 99%
See 1 more Smart Citation